Chikungunya: An emerging threat - Mahboob, Nabeela; Mamun, Kazi Taib; Iqbal, Hasina (Bangladesh Journal of Medical Microbiology, 2016)
Abstract not available Bangladesh J Med Microbiol 2016; 10 (2): 27-32